Abschätzung der Zahlungsbereitschaft für CO2-Einsparung: Ein Discrete-Choice-Experiment; Estimation of the Willingness to Pay for CO2 Savings - A Discrete Choice Experiment - Thore Holm-Mul̈ler; Uwe Latacz-Lohmann; Jens-Peter Loy; Norbert Schulz (German Journal of Agricultural Economics (GJAE), 2015)
– In this article the willingness to pay for different methods to save carbon dioxide emissions in northern Germany are examined by a Discrete Choice Experiment. The results of a latent-class estimation show, that the respondents could be disposed into four different classes. The membership to a certain class is mostly determined by the age and the common preferences for climate protection of the respondents. All respondents have the highest preference to save CO2 emissions by CO2-certificates, the lowest preferences exist for the carbon dioxide capture and storage method. The results vary between a willingness to pay for saving CO2 emissions of 644 exteuro/t and a willingness to accept a certain method for a compensation of 161 exteuro/t carbon dioxide.
Keywords: 330